Overview of the Assessment of Endothelial Function in Humans - Chia, Po Ying; Teo, Andrew; Yeo, Tsin Wen (Frontiers in Medicine, 2020)
The endothelium is recognized to play an important role in various physiological functions including vascular tone, permeability, anticoagulation and angiogenesis. Endothelial dysfunction is increasingly recognized to contribute to pathophysiology of many disease states, and depending on the disease stimuli, mechanisms underlying the endothelial dysfunction may be markedly different. As such, numerous techniques to measure different aspects of endothelial dysfunction have been developed and refined as available technology improves. Current available reviews on quantifying endothelial dysfunction generally concentrate on a single aspect of endothelial function, although diseases may affect more than one aspect of endothelial function. Here, we aim to provide an overview on the techniques available for the assessment of the different aspects of endothelial function in humans, human tissues or cells, namely vascular tone modulation, permeability, anticoagulant and fibrinolytic, and the use of body fluid biomarkers.